The influence of curing agents in the impact properties of epoxy resin nanocomposites - Amaro, Ana M. (2019)
This study investigates the impact properties (impact strength (IS) and impact energy (IE)) of epoxy resin nanocomposites (EPNCs) manufactured with different curing agents and reinforced with alumina nanoparticles (NPs). The NPs consisted on alpha alumina with irregular shapes (100 nm maximum size) pretreated with a silane agent. The weight fractions of alumina NPs were 1, 3 and 5 wt(%). Two different epoxy (EP) resins were studied and compared. The first one was cured and post cured with bis (4-aminophenyl) methane (DDM) and the second one was cured with 3-Dodec-2-enyloxolane-2,5-dione (DDSA) + 8-methyl-3a,4,7,7a-tetrahydro-4,7-methano-2-benzofuran-1,3-dione (MNA). Comparatively to the neat EP, and among the three NPs loadings used in this study, the EPNCs with 1 wt(%) showed the maximum improvement in IS and IE, around 78%(IE)-89%(IS) for DDM and 82%(IS)-93%(IE) for DDSA + MNA. EPNCs with 1 wt(%) cured with DDM present the best results for IS and IE, when compared with EPNCs cured with DDSA + MNA. IS and IE of EPNCs highly reduce at 3–5 wt(%).